Design of creative thinking test in geometry based on information processing taxonomy model - Hevy Risqi Maharani; Y L Sukestiyarno; St. Budi Waluya; Mulyono Mulyono (Universitas Islam Negeri (UIN) Mataram, 2018)
[English]: This paper describes how to develop a valid and reliable instrument for geometric creative thinking test based on the information processing taxonomy model. Using this model, geometry test can be classified in the level of creative thinking based on the information processing process of the mathematical knowledge they already have to solve problems according to the criteria at each hierarchical level. The development of the test instrument refers to Beyers (2011). A quantitative method was used to validate instruments through experts validation and instrument validation. The results showed that there was five geometry test that can be used to describe the student's creative thinking process at a different hierarchical level based on the information processing taxonomy. The results of this study can be a reference for teachers and other researchers to design mathematical test by paying attention to the hierarchical level of student's thinking abilities so that students with different abilities can solve problems which refer to their abilities. Keywords: Creative thinking,Geometry, Information processing taxonomy, Test design [Bahasa]: Artikel ini memaparkan tentang bagaimana menghasilkan instrumen yang valid dan reliabel untuk kemampuan berpikir kreatif geometris berdasarkan model taksonomi pemrosesan informasi. Dengan menggunakan model ini, soal geometri dapat diklasifikasikan dalam tingkatan berpikir kreatif siswa berdasarkan proses pengolahan informasi dari pengetahuan matematika yang telah mereka miliki untuk menyelesaikan masalah sesuai batas kriteria pada setiap tingkatannya. Pengembangan instrumen tes mengikuti langkah Beyers (2011). Metode kuantitatif digunakan untuk memvalidasi instrumen soal yang melalui tahap validasi ahli dan validasi instrumen. Hasil penelitian menunjukkan bahwa terdapat lima butir soal geometri yang dapat digunakan untuk mendeskripsikan proses berpikir kreatif siswa pada tingkatan hierarki yang berbeda berdasarkan model taksonomi pemrosesan informasi. Hasil penelitian ini dapat menjadi rujukan untuk guru maupun para peneliti lain untuk menyusun soal matematika dengan memperhatikan tingkatan hierarki kemampuan berpikir siswa agar siswa dengan berbagai kemampuan yang berbeda dapat mengerjakan soal sesuai dengan kemampuan yang mereka miliki. Kata kunci: Berpikir kreatif, Geometri, Taksonomi pemrosesan informasi, Desain tes